PARENTAL SMOKING FACTORS AND THEIR IMPACT ON ACUTE RESPIRATORY INFECTION (ARI) IN CHILDREN UNDER FIVE: LITERATURE REVIEW - Adeta Salsabila, Kalisha; Athallah Salman , Faiza; Aprilia Putri , Rizki; Rafa Maritza, Talitha; Aulia Salsabila , Najwa; Kharin Herbawani , Chahya (HEARTY, 2026)
Acute Respiratory Infection (ARI) is one of the leading causes of morbidity and mortality among children under five worldwide, including in Indonesia. A significant risk factor is exposure to cigarette smoke from parents, which has been shown to increase the likelihood of ARI in young children. This study aims to examine the relationship between exposure to cigarette smoke and the incidence of ARI in children under five, as well as to explore the factors that contribute to parental smoking behavior. The type of research used in this article is a literature review, structured according to the PRISMA methodology. The article identification process was carried out through three databases from PubMed, ScienceDirect, and GARUDA. From a total of 1.235 articles identified, a selection and analysis process was conducted, resulting in 12 articles that met the eligibility criteria for further review. The literature review of these 12 articles indicates a clear association between exposure to cigarette smoke from parental and household smoking and the prevalence of ARI in children under five. Several contributing factors to parental smoking, including low levels of knowledge, smoking culture, high stress levels, socioeconomic conditions, and weak enforcement of tobacco regulations, have been identified as key drivers that indirectly increase the risk of (ARI) in children under five. There is a notable relationship between exposure to cigarette smoke and the incidence of ARI in children under five, which is influenced by parental smoking patterns.